Fruit Oils: Chemistry and Functionality - Ramadan, Mohamed Fawzy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Fruit Oils: Chemistry and Functionality presents a comprehensive overview of recent advances in the chemistry and functionality of lipid bioactive phytochemicals found in fruit oils. The chapters in this text examine the composition, physicochemical characteristics and organoleptic attributes of each of the major fruit oils. The nutritional quality, oxidative stability, and potential food and non-food applications of these oils are also extensively covered. The potential health benefits of the bioactive lipids found in these fruit oils are also a focus of this text. For each oil presented, the levels of omega-9, omega-6 and omega-3 fatty acids are specified, indicating the level of health-promoting traits exhibited in each. The oils and fats extracted from fruits generally differ from one another both in terms of their major and minor bioactive constituents. The methods used to extract oils and fats as well as the processing techniques such as refining, bleaching and deodorization affect their major and minor constituents. In addition, different post-processing treatments of fruit oils and fats may alert or degrade important bioactive constituents. Treatments such as heating, frying, cooking and storage and major constituents such as sterols and tocols are extensively covered in this text. Although there have been reference works published on the composition and biological properties of lipids from oilseeds, there is currently no book focused on the composition and functionality of fruit oils. Fruit Oils: Chemistry and Functionality aims to fill this gap for researchers, presenting a detailed overview of the chemical makeup and functionality of all the important fruit oils. .
Part 1: General aspects -- chap1-Chemistry and functionality of fruit oils-An introduction -- Chap 02-Grading, labeling and standardization of edible oils -- Chap 03-Fruit oils in Kosovo: chemistry and functionality -- Chap04-Olive oil properties from technological aspects to dietary and health claims -- Part 2: Oils from fruit nuts -- Chap 05-Virgin walnut (Juglans regia L.) oil -- Chap 06-Almond (Prunus dulcis) oil -- Chap 07-Virgin pistachio (Pistachia vera L.) oil -- Chap 08-Chestnut (Castanea sativa) oil -- Chap 09-Coconut (Cocos nucifera) oil -- Chap 10-Hazelnut (Corylus avellana) oil -- Chap 11- Tiger nut (Cyperus esculentus L.) oil -- Part 3:Fats from fruit seeds and pulp -- Chap 12-Rambutan (Nephelium lappaceum) fats -- Chap13 -- Chyuri butter (Diploknema butyracea) seed fat -- Chap 14-Madhuca longifolia butter -- Part 4: Oils from fruit seeds and pulp -- Chap 15: Chia (Salvia hispanica) oil -- Chap 16-Argan [Argania spinosa (L.) Skeels] oil: extraction, composition and uses -- Chap 17- Avocado (Persea americana Mill.) oil -- Chap 18- Gac (Momordica cochinchinensis (Lour) Spreng.) oil -- Chap 19-Goldenberry (Physalis peruviana) oil -- Chap 20-Olive (Olea europea L.) oil -- Chap 21-Vaccinium genus berry waxes and oils -- Chap 22-Crambe abyssinica Hochst. Oil -- Chap 23- Kenaf (Hibiscus cannabinus L.) seed oil -- Chap 24-Apple (Malus pumila) seed oil -- Chap 25- Apricot (Prunus armeniaca L.) oil -- Chap 26- Citrus oils -- Chap 27- Guava (Psidium guajava) oil -- Chap 28- Mango (Mangifera indica L.) Seed Oil -- Chap 29- Passion fruit (Passiflora spp.) seed oil -- Chap 30- Bael (Aegle Marmelos) Oil -- Chap 31- Papaya (Carica papaya L.) Seed Oil -- Chap 32-Mongongo/Manketti (Schinziophyton rautanenii) oil -- Chap 33- Bauhinia purpurea seed oil -- Chap 34- Pongamia pinnata seed oil -- Chap 35-Cranberry seed oil -- chap 36-Dragon (Hylocereus megalanthus) seed oil -- Chap 37- Pomegranate (Punica granatum) seed oil -- Chap 38-Sandalwood (Santalum album) oil -- Chap 39 -- Watermelon (Citrullus lanatus) oil -- Chap 40 -- Semecarpus anacardium oil -- Chap 41-Pumpkin seed (Cucurbita pepo L.) Oil -- Chap 42-Palm (Elaeis guineensis Jacq.) Oil -- Chap 43- Rosehip (Rosa canina L.) oil -- Chap 44- Date (Phoenix dactylifera L.) seed oil -- Chap 45-Celastrus paniculatus oil -- Chap 46- Black seed (Nigella sativa) oil -- Chap 47-Pear (Pyrus communis) seed oil -- Chap 48- Amla (Emblica officinalis L.) Oil.
Keywords: Food science; Biochemistry; Chemistry, Organic; Food Science; Biochemistry; Organic Chemistry